Ideas, Concepts, and Reality - John W. Burbidge (McGill-Queen's University Press, 2013)
When we approach the study of logic for the first time, we encounter a strange paradox. the Oxford Concise Dictionary1 defines logic as the â€œscience of reasoning, proof, thinking, or inference; â€¦ [a] chain of reasoning, correct or incorrect use of reasoning, ability in reasoning.â€ the gerunds2 in the definition â€“ â€œreasoningâ€ and â€œthinkingâ€ â€“ suggest the study of certain activities that the intellect or mind performs. But the sophisticated discipline designated by this definition makes no mention of mental operations, nor does it nurture skills that would make thinking more effective. rather, it defines a number of symbols, stipulates how to fit normal thoughts into those symbols, specifies particular ways of using them, and provides standards to ensure that an argument (which is now simply a pattern of such symbols) is valid.3 it rigorously excludes any suggestion of an actual process of reasoning. there have been a number of attempts to modify this stark contrast. Universities have developed courses with such names as â€œpractical reasoning,â€ â€œargumentation,â€ and â€œinformal logic,â€ which concentrate on inferences that do not satisfy formalistsâ€™ strict criteria of validity. these train students to assess the reliability and relevance of premises, the strength of grounds, and the temptations that arise from rhetorical devices that sound like good reasons but are in fact deceptive. and scholars have undertaken much research into the details of these operations. none the less this whole subdiscipline lives in the shadow of its more rigorous counterpart â€“ a poor second best that may be useful at times when strict validity is not possible but whose imperfections always point towards its perfect prototype. it is almost as if its contact with the messiness of actual thinking soils and besmirches it. this discrepancy between the pure science of logical validity and the actual processes of human reasoning has many sources. aristotle was the first to identify certain forms of good reasoning worthy of investigation irrespective of the content that thought introduces. and his schema of valid syllogisms, later augmented by the stoic philosophers, served as the core of all logical studies until the midnineteenth century. But the contrast between form and content became absolute only in the writings of Gottlob Frege.